2005
DOI: 10.1167/iovs.05-0019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetic Retinopathy in Urban India: The Chennai Urban Rural Epidemiology Study (CURES) Eye Study, I

Abstract: This study shows that the prevalence of diabetic retinopathy is lower in urban South Indians than in other ethnic groups. However, due to the large number of diabetic subjects, DR is likely to pose a public health burden in India; hence, routine retinal examination is mandatory to detect DR in the early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
302
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(366 citation statements)
references
References 30 publications
47
302
16
1
Order By: Relevance
“…Overall, prevalence of DR in hospital based studies [7,11], including present study was higher as compared to those in population based epidemiological studies [8,12,13]. This observation may be attributed to the fact that there was a referral bias among the diabetic patients who were reported to tertiary care centres.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Overall, prevalence of DR in hospital based studies [7,11], including present study was higher as compared to those in population based epidemiological studies [8,12,13]. This observation may be attributed to the fact that there was a referral bias among the diabetic patients who were reported to tertiary care centres.…”
Section: Resultscontrasting
confidence: 48%
“…Raman et al, found a prevalence of 18% in diabetic population, whereas Agrawal RP et al, found a prevalence of 28.9% in type 2 diabetic population [6,7]. Although various population and hospital based studies have been conducted in northern [7] and southern [8] parts of India to estimate the prevalence of DR in type 2 diabetic population, there is a paucity in the literature regarding the prevalence of DR in western India. With above context, a hospitalbased, cross-sectional study was designed to find out prevalence of DR and effect of duration of diabetes on severity of DR in western Indian, type 2 diabetic population.…”
Section: Introductionmentioning
confidence: 99%
“…5 Population data on micro and macro vascular complications of diabetes are available in urban India. [6][7][8][9][10] However, such data were not available in rural India. This is largely because in rural areas, diabetes remains a neglected field, as awareness levels and accessibility to diabetes health care remains woefully inadequate.…”
Section: Symposiummentioning
confidence: 99%
“…7 Globally, DM is the leading cause of blindness, especially in developing countries. 8,9 Hyperglycemia, glycation of hemoglobin, and duration of diabetes disease are among multiple factors involved in the development of diabetic retinopathy (DR). 9,10 In addition, retinal ischemia and OS are important processes in developing DR. Of much importance, it has been reported that hyperglycemia per se lead to increased generation of FRs and OS.…”
Section: Introductionmentioning
confidence: 99%